Solve the equation x^6 + 26x^3 − 27 = 0

While this equation may look complicated, it's actually much easier than it looks - this equation is called a hidden quadratic. This is because it can be rewritten and solved the same way you would solve a quadratic. This becomes clear when you compare it to how a quadratic looks: a w^2 + b w + c. Since the power of the first term is double the power of the second term and the last term is a constant, it can be identified as a hidden quadratic and using the substitution w = x^3, can be rewritten as one (this will be an equation in terms of w).This can be done as follows: x^6 + 26x^3 -27 = 0 (=>) w^2 + 26w -27 = 0 (=>) (w+27) (w-1) = 0 Here is where we substitute x^3 back in to get the equation in terms of x again! (=>) (x^3+27)(x^3-1) = 0 (=>) x^3 = -27 and x^3 = 1 By cube rooting -27 and 1, we get the solutions x=-3 and x =1

Answered by Saachi P. Maths tutor

4457 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

Explain the basics of projectile motion


Determine the integral: ∫x^(3/4)dx


Find the gradient of the tangent to the curve with the equation y = (3x^4 - 18)/x at the point where x = 3


A child of m1=48 kg, is initially standing at rest on a skateboard. The child jumps off the skateboard moving horizontally with a speed v1=1.2 ms^-1. The skateboard moves with a speed v2=16 ms^-1 in the opposite direction. Find the mass of the skateboard.


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences